A new species of Trimma (Pisces: Gobiidae) from western Thailand, north-eastern Indian Ocean - Winterbottom, Richard (Zootaxa, 2021)
A new species of Trimma is described from the islands just off the Thailand coast near Phuket. Trimma ukkriti n.sp. lacks scales on the cheek and opercle, but has ctenoid scales in the midline of the nape, has an elongate second spine of the first dorsal fin which reaches posteriorly to between the base of the spine and the base of the 4th ray of the second dorsal fin when adpressed, 19–20 pectoral-fin rays with 6–13 branched rays in the middle of the fin, an unbranched 5th pelvic-fin ray, which is 48–67% the length of the 4th ray, a U-shaped interorbital trench with no fleshy median ridge, a poorly developed postorbital trench ending at the 5th papilla in row p (which has 6 papillae in total), and row c beneath the eye consists of 6 papillae. When live and freshly collected, the species is very similar in appearance to T. okinawae and T. readerae, with orange to red spots on the head and body.